خاندانی نظام کے استحکام میں تربیتِ اخلاق کا کردار: سیرت طیبہﷺ کے تناظر میں ایک مطالعہ (Al-Qamar, 2024)
Family is the basic unit of the society and it makes a strong society. All members of the family are the strong pillars that form this basic social unit. The stronger and more stable this unit is, the better and stronger the society will be. Protection of family values is what helps the society in order of life. Contemporary demands have changed the family system from collectivism to individualism, it has faced many problems. Many institutions that were collectively meaningless were considered defects. Ethics and moral values are very important in Islam. Therefore, the Prophet (ﷺ) was sent to protect and elevate noble morals. Being a role model for humanity in all matters, the teachings of Seerat Tayyaba (ﷺ) also guide humanity. The purpose of this article is to highlight the Prophetic method of teaching ethics and moral values in the family system so that high ethics can be created in the training in the family system.
Keywords: Family System; Training; Ethics